Computational Modeling of Objects Presented in Images Fundamentals, Methods and Applications - Di Giamberardino, Paolo; Iacoviello, Daniela; Natal Jorge, Renato; Tavares, João Manuel R. S. (Lecture Notes in Computational Vision and Biomechanics, 2014)
This book contains extended versions of selected papers from the 3rd edition of the International Symposium CompIMAGE. These contributions include cover methods of signal and image processing and analysis to tackle problems found in medicine, material science, surveillance, biometric, robotics, defence, satellite data, traffic analysis and architecture, image segmentation, 2D and 3D reconstruction, data acquisition, interpolation and registration, data visualization, motion and deformation analysis, and 3D vision.